Corporate social responsibility, financial performance and risk in Indonesian natural resources industry. Issue 1 (2nd January 2019) - Devie, Devie; Liman, Lovina Pristya; Tarigan, Josua; Jie, Ferry
Abstract : Purpose: With an attempt to give a deeper explanation regarding the manifestation of socially and environmentally responsible cultures among Indonesian natural resources industry, this paper aims to highlight the empirical confirmation on the correlation of corporate social responsibility (CSR), corporate financial performance (CFP) and risk. Likewise, corporate risk's role as a mediating variable in the indirect effect of CSR on CFP is also examined. Design/methodology/approach: Kinder, Lydenberg and Domini's (KLD) measurement approach is used as a basis to assess social responsibility activities as it gives more social rating transparency. CFP captures both accounting- and market-based measurements, whereas volatility of stock return is adopted as a proxy of firm risk. Partial least squares analysis is conducted on 40 Indonesian listed firms in natural resources sector, with observation years from 2008 to 2016. Findings: It is revealed that CSR positively affects CFP, although the correlation is stronger in the long run. Significant negative influence to risk is also discovered. However, risk has a significant adverse correlation with CFP when two years' lagged value is used. Hence, CSR affects CFP through risk in the long-term, both directly and indirectly. Practical implications: The empirical result suggests that CSR serves as a tool in managing the risk of enterprises and performance, especially in the long-term. Accordingly, firms should incorporate CSR as a strategic investment and manage a strong relationship with stakeholders. Originality/value: This report expands further prior works and contributes to CSR and financial management literature by discovering the true nature of CSR effects as an investment in the future. This is the first study which tests and proves that CSR in Indonesian natural resources industry plays a significant role as a strategic risk management instrument that leads to a sustainable and long-lasting financial performance.